Relationship Between Work Ethics and Organizational Commitment Among Employees at Furniture Manufacturer in Johor - Fadillah Ismail; Mohd Yusof, Farahwahidah (Advances in Humanities and Contemporary Studies, 2024)
This study aims to examine the relationship between work ethics and organizational commitment among employees at a furniture manufacturer in Muar and Segamat, Johor. It investigates four objectives: identifying the level of work ethics and organizational commitment, analyzing their relationship, and determining the most dominant dimension of work ethics influencing organizational commitment. Four dimensions of work ethics (benevolence, integrity, prudence, and respect) and three dimensions of organizational commitment (affective, continuance, and normative) were measured. The study involved 209 respondents, using questionnaires and SPSS Version 22.0 for data analysis. Descriptive analysis was employed for demographic data, while Pearson Correlation and Regression Analysis were used to explore relationships and influence, respectively. Results indicated high levels of work ethics and organizational commitment, with a strong positive correlation between them (r=0.871). Benevolence emerged as the most dominant dimension of work ethics influencing organizational commitment (β=0.786). These findings underscore the critical role of benevolence in enhancing organizational commitment, suggesting that fostering an environment that emphasizes kindness and goodwill among employees can significantly strengthen their loyalty and commitment to the organization.